Prevalence of COVID-19 and associated factors among healthcare workers in the war-torn Tigray, Ethiopia. - Bisrat Tesfay Abera; Teklay Gebrecherkos; Migbnesh Gebremedhin Weledegebriel; Girmatsion Fisseha Abreha (PLoS ONE)
Background The Coronavirus disease 2019 (COVID-19) has put an enormous encumbrance on the healthcare system and healthcare workers (HCWs) worldwide, particularly in war-torn areas. As the world strives to end the pandemic, knowing the magnitude of the infection and its contributing factors in fragile settings is critical to prevent further waves of the pandemic. Methods Using rapid diagnostic tests (RDTs), a facility-based cross-sectional study was conducted to assess the prevalence of COVID-19 and its associated factors. The study was conducted among 326 unvaccinated HCWs in two hospitals in Tigray, Ethiopia from. The study period was from June 26 to December 31, 2021. Descriptive statistics were used to analyze the characteristics of study participants and the magnitude of COVID-19 while multivariate logistic regression was applied to assess factors affecting COVID-19 infection among HCWs. Results The seroprevalence of COVID-19 among HCWs in the war-torn region of Tigray was 52.4% and 56.5% using Cellex and INNOVA antibody RDTs, respectively. The point prevalence, using Abbot Antigen test, was 14.2%. The overall infection prevention and control practice (IPC) and facility preparedness was poor with >85% of the HCWs reporting not wearing eye goggle/face shield and respirator in activities that needed transmission-based precautions; none of the participants reporting as having separate waste disposal system for COVID-19 cases; and only 56.8% reporting as having an isolation area during the time of testing. In the multivariate analysis, not having isolation area (AOR = 19.6, 95% CI: 7.57-50.78), re-using of personal protective equipment (PPE) (AOR = 3.23, 95% CI: 1.54-6.77), being symptomatic (AOE = 2.4, 95% CI: 1.02-5.67), and being a medical doctor, doctor of dental surgery, and anesthetist (AOR = 3.64, 95% CI: 1.05-12.66) were significantly associated with having at least one positive result. Conclusions Shortage of PPE supply, poor IPC practice, suboptimal facility preparedness, and low vaccination coverage in the region contributed to the high rate of COVID-19 infection among HCWs observed in this study.